Olaparib-Induced Immune-Mediated Liver Injury. Issue 1 (10th January 2022) - Alshelleh, Mohammad; Park, Jennifer; John, Veena; Rishi, Arvind; Bernstein, David; Roth, Nitzan
ABSTRACT: Immune-mediated drug-induced liver injury can be triggered by multiple classes of medications including immunotherapies. Olaparib is a first-in-class oral inhibitor of poly (adenosine diphosphate-ribose) polymerase (an enzyme involved in DNA replication and repair) that is approved as maintenance treatment in platinum-sensitive, epithelial ovarian, tubal, or primary peritoneal cancers with breast cancer 1/2 mutation. We report the first case in the United States of an acute and severe liver injury with associated jaundice and liver synthetic dysfunction secondary to olaparib. The liver injury was resolved with drug cessation and treatment with prednisone taper.